Metachromatic leukodystrophy - Gieselmann, Volkmar (Henry Stewart Talks, 2007)
Metabolic defect in metachromatic leukodystrophy, Genetics, Genotype/phenotype correlations, Biochemical consequences of selected mutations, Diganostic problems due to arylsulfatase A pseudodeficiency, Gene therapy and enzyme replacement trials in an animal model
Archived at 2020/08/13